The Role of Marketplaces in Assisting MSME Growth Using the Systematic Literature Review Method - Sari, Rizqi Kurnia; Syaputra, Muhammad Adie (Journal of Applied Informatics and Computing, 2025)
Digital technology provides significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to grow and innovate, contributing to national economic growth. This study aims to analyze the role, impact, and supporting factors of marketplaces in fostering MSME development in Indonesia. Using the Systematic Literature Review (SLR) method, 103 journals were identified through Publish or Perish via Crossref for the 2019–2024 period. These journals were then filtered down to 40 journals selected for descriptive analysis. The 2019–2024 timeframe was chosen as it reflects a significant surge in marketplace adoption during the COVID-19 pandemic.The findings reveal that marketplaces significantly enhance MSMEs by increasing market reach by up to 40%, improving operational efficiency through a 30% reduction in order processing time, and building customer trust through reviews and ratings. The study also highlights the importance of supporting factors such as adequate digital infrastructure, digital literacy, and support from the government and platform providers. However, challenges such as limited internet access, low digital literacy, high commission fees, and intense competition with larger brands hinder the optimal use of marketplaces by MSMEs.This study recommends several practical solutions, including strengthening digital infrastructure, subsidizing internet costs, providing digital literacy training, and offering special promotion programs for small MSMEs. Although this study relies on secondary data, the findings provide relevant insights for policymakers, platform providers, and MSME actors. Further studies using primary data are needed to enhance the generalizability of these findings.